Fertility Choices of Australian Couples - Blacklow, P (My University, 2006)
This paper examines the demand and supply factors that effect how many children a couple will have. It estimates the wage over working women to use as the potential wage for all women to avoid missing data and wage endogeneity problems. It estimates the total number and probability of having a certain number of children using a range of variables capturing preferences and demand and supply economic variables and other variables. OLS, Poisson, multinomial Logit, and Sequential Logit are used to examine which factors are significant in effecting fertility choices.
School of Economics and Finance, University of Tasmania, Discussion Paper
Keywords: Families; Families -- Fertility; Families and relationships; Families and relationships